The Impact of Islamic Financial Inclusion and Digital Payment Adoption on the Economic Resilience of Muslim MSMEs Amid Pressure from the Rupiah's Depreciation - Indriyani Pamenangan; Verta Destania Kusuma Dewi; Khoirul Anwar; Ahmad Dzunnuroin; Tuti Nadhifah (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2026)
Muslim Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face serious sustainability challenges due to inflationary pressures and rising production costs following the depreciation of the Rupiah. This study aims to analyze the synergy between Islamic financial inclusion and the adoption of digital payments as a strategic mitigation mechanism for businesses in facing these macroeconomic shocks. Through a systematic literature review of 11 scientific articles (2021–2025), this study synthesizes the synergy between financial digitalization and Islamic financial inclusion as an operational resilience mechanism for Muslim MSMEs. The synthesis results show that the adoption of digital payments significantly improves cash flow efficiency and operational transparency, while Islamic financial inclusion provides a foundation for stability through the principles of fairness, partnership, and ethical risk management. This synthesis confirms that the integration of these two instruments is not merely a transaction tool but a crucial operational instrument for building the resilience of Muslim MSME businesses to fluctuations in production costs due to inflationary pressures. In conclusion, the synergy between Islamic financial inclusion and the adoption of digital payments is an effective mitigation strategy for Muslim MSMEs. Therefore, policies to strengthen the competitiveness of business actors need to focus on optimizing access to and implementing an integrated financial system to ensure business sustainability amidst global economic uncertainty.